Review: Plant cell wall biochemical omics: The high-throughput biochemistry for polysaccharide biosynthesis. (September 2019) - Faik, Ahmed; Held, Michael
Graphical abstract: Highlights: Biochemistry of plant cell wall biosynthesis lacks high-throughput methods. Overview of new high-throughput technologies to benefit plant cell wall biosynthesis. Use of protein array technology in enzyme assays and protein–protein interaction. Adapting recent advances in analytical chemistry for rapid product identification. Abstract: Progress in the functional biochemical analysis of plant glycosyltransferases (GTs) has been slow because plant GTs are generally membrane proteins, operate as part of larger, multimeric complexes, and utilize a vast complexity of substrate acceptors. Therefore, the field would benefit from development of adequate high throughput expression as well as product detection and characterization techniques. Here we review current approaches to tackle such obstacles and suggest a new path forward: nucleic acid programmable protein arrays (NAPPA) with liquid sample desorption ionization (LS-DESI-MS) mass spectrometry. NAPPA utilizes in vitro transcription and translation to produce epitope-tagged fusion proteins from cloned GT cDNAs. LS-DESI is a soft ionization technique that allows rapid and sensitive MS-based product characterization in situ . Coupling both approaches provides the opportunity to examine individual GT functions as well as protein–protein interactions. Furthermore, advances in automated oligosaccharide synthesis and lipid nanodisc technology should allow testing of plant GT activity in presence of numerous substrate acceptors and lipid environments in a high throughput fashion. Thus, NAPPA-DESI-MS has great potential to make headway in biochemical characterization of the large number of plant GTs.